Islamic Inheritance Law In Indonesia and Malaysia: Gender Equality Through Consensual Modification - Oman Sudrajat; Wasehudin Wasehudin; Itang Itang; Yuyun Rohmatul Uyun; Hadi Peristiwo (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
Islamic inheritance law prescribes a two-to-one ratio between male and female heirs, yet contemporary socioeconomic transformations have prompted scholarly inquiry into possibilities for gender-equitable distribution. This study examines how Indonesia and Malaysia, as the largest Muslim-populated Southeast Asian nations, approach consensual modification of inheritance shares to achieve equality between male and female offspring. This research employs a qualitative comparative normative approach, examining primary legal materials including the Indonesian Compilation of Islamic Law, Malaysian state-level Islamic inheritance enactments, Quranic provisions, and scholarly jurisprudential literature. The analysis utilizes maqasid al-shariah (objectives of Islamic law) as the theoretical framework to evaluate both legal systems. Indonesia offers significant flexibility through Article 183 of the Compilation of Islamic Law, which permits heirs to reach consensual agreements for share equalization at the initial distribution stage, reflecting the cultural emphasis on musyawarah (deliberation). Conversely, Malaysia maintains formal faraid compliance, allowing consensual modifications only after Syariah Court completion of formal share determination through mechanisms such as taksim taradi. The divergent approaches reflect different jurisprudential orientations: Indonesia prioritizes adaptive interpretation responsive to social dynamics, while Malaysia emphasizes preservation of classical calculations. Both systems maintain the two-to-one ratio as baseline while accommodating practical flexibility through different mechanisms, demonstrating that justice in Islamic inheritance is contextual and can align legal outcomes with contemporary family welfare without abandoning foundational principles.